2012
DOI: 10.5039/agraria.v7i4a1434
|View full text |Cite
|
Sign up to set email alerts
|

Produção de gases e digestibilidade in vitro de silagens de maniçoba aditivadas com coproduto vitivinícola

Abstract: RESUMOAvaliaram-se a cinética da produção de gases e a digestibilidade in vitro da matéria seca (DIVMS) das silagens de maniçoba com diferentes inclusões do coproduto de vitivinícolas desidratado (CVD) e se confeccionaram 32 silos experimentais da parte aérea da maniçoba, distribuídos em quatro tratamentos (0, 8, 16 e 24% de inclusão do CVD) perfazendo oito repetições. A cinética da fermentação foi avaliada pela técnica in vitro semiautomática de produção de gases. O potencial máximo da produção de gases dos c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…According to Vans Soest (1994), non-brous carbohydrates are available for microbial degradation and have a rapid rate of fermentation, while brous carbohydrates need to be colonized by microorganisms to be degraded, making fermentation slow. Silva et al (2014), and Rodrigues et al (2012) reported the behavior similar to the present experiment, where higher rates of degradation of non-brous fractions were observed in relation to brous ones.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to Vans Soest (1994), non-brous carbohydrates are available for microbial degradation and have a rapid rate of fermentation, while brous carbohydrates need to be colonized by microorganisms to be degraded, making fermentation slow. Silva et al (2014), and Rodrigues et al (2012) reported the behavior similar to the present experiment, where higher rates of degradation of non-brous fractions were observed in relation to brous ones.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, it was observed in Fig. 2B shorter colonization time (0.01 hours) in silages harvested at 95 days added with 40 g of molasses, which may be an effect of molasses on bacterial growth colonization (Rodrigues et al, 2012). Therefore, the reduction in colonization time (LAG) is in uenced by the type of substrate used in fermentation and by the physical and chemical characteristics of the food cell wall (Tomich et al, 2011).…”
Section: Discussionmentioning
confidence: 90%